Mekanisme fouling pada membran mikrofiltrasi mode aliran searah dan silang - Iqbal Shalahuddin; Yusuf Wibisono (Jurnal Rekayasa Proses, 2019)
Microfiltration is a low pressure driven membrane process of about 1 bar trans-membrane pressure which is used frequently for separating dissolved particles within 0.1 to 10 μm size. Microfiltration membranes are utilized in water and wastewater treatment processes either during pretreatment, treatment, or post-treatment steps. Moreover in bioprocessing, microfiltration is used in upstream process for substrate sterilization or in downstream process for microbial suspension separation. Fouling is one major concern of membrane filtration processes, including microfiltration. In this article, the fouling mechanism on microfiltration membrane is explained based on the blocking model refer to cake filtration due to the complexity of fouling phenomena. Fouling mechanism on dead-end and cross-flow modes microfiltration are explained, and basically distinguished into four different mechanisms, i.e. complete blocking, standard blocking, intermediate blocking and cake filtration. The proposed models are based on constant pressure operation on the uniform membrane pores, both for dead-end and cross-flow modes. Cross-flow mode, however, is restricted on the beginning of filtration until critical flux condition is reached.